CLINICAL, LABOLATORY FINDINGS AND EPIDEMIOLOGY OF PULMONARY DISEASES DUE TO NONTUBERCULOUS MYCOBACTERIA AT NATIONAL LUNG HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objectives: Description of clinical findings, laboratory testing and epidemiology of patients withNTM pulmonary disease at the National Lung Hospital from 2017-2021.Methods: Cross-sectional study on 136 patients diagnosed with NTM-PD at National Lung Hospitalfrom 1/2017 to 6/2021.Results: The average age of 136 patients was 58.2 ± 15.4 years old, the patients more than 60 yearsold accounted for the highest rate of 44.1%. The proportion of M.abscessus, M.intracellulare andM.avium were 45,45%, 35,66% and 11,19%, respectively. 40% patients had previous TB treatment.16% patients had diseases related to lung structure (COPD, bronchiectasis). The major of patientsare detected 2-4 months from the time of admission to the time of confirmed diagnosis. Coughwith production more than 2 weeks is most common (>90%). 50.7% of cases had smear positive.Nodular and bronchiectasis on chest CT were more common in MAC-PD patients (61.2%) than inM. abscessus-PD ones (47.7%) (p0.05).Conclusion: The clinical symptoms of NTM-PD are diverse, variable and non-specific because theycan appear in many different respiratory diseases.
Keywords: NTM-PD, MAC, M.abscessus, M.intracellulare, M.avium.